Centrizonal hepatocyte dropout in allograft liver biopsies: a clinicopathological study. Issue 4 (7th February 2022) - Bosch, Dustin E; Swanson, Paul E; Yeh, Matthew M
Abstract : Aims: Centrizonal hepatocyte dropout has been described in diverse liver pathologies, including viral hepatitis, venous outflow obstruction, and allograft cellular rejection. However, its clinical significance remains uncertain. Methods and results: We designed a clinicopathological study of 206 allograft liver biopsies with centrizonal hepatocyte dropout. Centrizonal hepatocyte dropout was associated most frequently with cellular rejection ( n  = 62), asymptomatic/protocol biopsies ( n  = 56), immediate post‐transplantation biopsies ( n  = 21), biliary obstruction ( n  = 14), and viral hepatitis ( n  = 13). The differential diagnosis is informed by timing post‐transplantation, biliary imaging and laboratory test results. 'Cholestatic' and 'hepatocytic' laboratory patterns were associated with biliary obstruction and cellular rejection, respectively. A mixed pattern peaking after biopsy was observed in viral hepatitis cases. In the context of cellular rejection, dropout was not associated with the time interval to normalisation of serum alanine aminotransferase (ALT), but was associated with shorter transplant‐free survival (hazard ratio 4, P  = 0.01) than that of histological severity‐matched controls. In time zero allograft biopsies, time to ALT normalisation was prolonged (median, 15 versus 11 days, P  = 0.002) in allografts with centrizonal dropout, with no effect on retransplant‐free survival. Conclusions: Centrizonal hepatocyte dropout has low clinicopathological diagnostic specificity. However, it correlates with adverse clinical outcomes in allograft cellular rejection and time zero biopsies. Abstract :